What do social work journals and research networks tell us? Expressions and conceptions around the construction of disciplinary knowledge - Muñoz-Arce, Gianinna; Rubilar-Donoso, Gabriela; Matus-Sepúlveda, Teresa; Parada-Ballesteros, Paula (Critical Proposals in Social Work, 2021)
In this article we address the question of the construction of knowledge in social work by analyzing academic journals and research networks as key dimensions in the dissemination of the intellectual production of the discipline. Singularities are identified and conceptual approaches, as well as methodological and ethical standards, are critically problematized. The configuration of the teams, the thematic lines, the geographical location and the political scope of the debates promoted in journals and research networks are examined. It is proposed that the way in which knowledge is produced in social work is "insular" or geopolitically concentrated, with observable asymmetries on a conceptual and methodological basis, diversity in the configuration of teams and with different public impact scopes. It is observed that journals tend to reproduce endogenic logics; while the research networks that work with decentralized or heterarchical logics are oriented to open spaces for relationships and to exert influence in the public debate, as well as to manifest concerns about the training of future researchers from the discipline. These findings make it possible to problematize the logic of the policies to promote research and dissemination of knowledge -public funds, incentives, access policies- and to project the challenges of social work in terms of its positioning and contributions to the debate on this matter.